The Sin of Reproducing: Intersectional Marginalization in N. K. Jemisin's The Fifth Season. Issue 3 (1st December 2022) - Warren, Hannah V.
Abstract : Using monster theory, critical race theory, and Black feminist scholarship to closely analyze the rhetorical and physical violence perpetrated against the central character in N. K. Jemisin's The Fifth Season (2015), this essay examines how the marginalization Essun/Syenite/Damaya experiences derives from her intersectional identities as both an orogene and a woman, along with how secondary characters enforce this marginalization based on their fears and desires in the novel's apocalyptic landscape. Although the ostracism in this text does not rely specifically on race, it nonetheless fulfills the same function as racism in the narrative's world, an oppression intersecting with the primary character's gender and ability to produce future labor. While Jemisin offers alignments with orogenic oppression and America's historical subjugation of Black bodies, she also emphasizes resistance and hope.